ACETYLCHOLINESTERASE INHIBITION-BASED LARVICIDAL ACTIVITY OF CARICA PAPAYA LEAF AND DURIO ZIBETHINUS PEEL EXTRACTS AGAINST AEDES AEGYPTI: A PROBIT AND GC–MS APPROACH - Aulie Iffatush Shofwah; Boas Obama Sitohang; Agung Gumelar; Agus Rochmat; Ahmad Bukhari (Penelitian dan Pengembangan Ilmu, 2025)
This study investigated the biolarvicidal potential of Carica papaya Linn leaf extract and Durio zibethinus Murr peel extract against Aedes aegypti mosquito larvae, the primary vector of dengue fever. Extracts were prepared via maceration with 70% ethanol. Toxicity assessments were conducted on third-instar larvae, evaluating individual and combined extract effects across various concentrations. Larval mortality was recorded at 24 and 48 hours, and the LC50 value was determined using Probit analysis. Bioactive compounds were identified through Gas Chromatography-Mass Spectrometry (GC-MS). Results indicated that a 50%:50% combination of papaya leaf and durian peel extracts, as well as a 25% papaya:75% durian ratio, achieved a notable 70% larval mortality. While these combinations demonstrated high efficacy, further statistical analysis, such as Abbott's formula, is required to confirm synergistic interactions definitively. The calculated LC50 of 131.95 ppm classified the extracts as toxic to A. aegypti larvae. GC-MS analysis of papaya leaf extract revealed neurotoxic and hormonal-disrupting compounds, including Prilocaine and Lidocaine. The study concludes that papaya leaf extract possesses superior larvicidal properties compared to durian peel extract, likely attributable to its significant alkaloid content, which inhibits acetylcholinesterase enzyme activity.